2021
DOI: 10.1097/dad.0000000000001812
|View full text |Cite
|
Sign up to set email alerts
|

Sebaceous Carcinomas: A Clinicopathological Comparison of Ocular and Extraocular Variants

Abstract: Sebaceous carcinomas (SC) are rare tumors and are currently classified into ocular and extraocular variants. Both variants of SC have very different clinical behavior and different histomorphologic appearance; however, published data are confounding as literature describes prognosis of both variants is similar or even that extraocular variants are more aggressive. In this study we evaluated the clinical and the histopathology of ocular and extraocular SC to confirm the difference between them. We performed a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…SCs can be categorized into well-differentiated and poorly-differentiated varieties based on the extent of sebocyte differentiation. 16 Poorly-differentiated lesions pose a challenge to pathologists as they lack any conspicuous sebocyte differentiation. Microscopic examination of the well-differentiated specimen showed that the sebocytes and duct epithelial cells formed many irregular, asymmetric sebaceous lobules.…”
Section: Discussionmentioning
confidence: 99%
“…SCs can be categorized into well-differentiated and poorly-differentiated varieties based on the extent of sebocyte differentiation. 16 Poorly-differentiated lesions pose a challenge to pathologists as they lack any conspicuous sebocyte differentiation. Microscopic examination of the well-differentiated specimen showed that the sebocytes and duct epithelial cells formed many irregular, asymmetric sebaceous lobules.…”
Section: Discussionmentioning
confidence: 99%
“…Sebaceous carcinoma can be classified as ocular or extraocular depending on its tissue of origin, a distinction that is relevant in presentation, pathology, and treatment [ 1 , 2 ]. Up to 75% of cases of sebaceous carcinoma arise from the ocular adnexa, most often on the upper lid from the Meibominan glands of the tarsus or Zeis glands of the eyelashes [ 1 , 2 , 5 ]. Extraocular sebaceous carcinoma frequently arises from the skin of the head and neck, corresponding to the density of sebaceous glands [ 1 , 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extraocular sebaceous carcinoma is more often associated with a better prognosis than ocular sebaceous carcinoma, although existing literature does include conflicting conclusions. Extraocular sebaceous carcinoma has a reduced tendency for metastasis to regional lymph nodes and reduced rates of recurrence relative to ocular sebaceous carcinoma [ 5 , 9 ]. Ocular sebaceous carcinomas can be assessed using the American Joint Committee on Cancer (AJCC) staging system, while extraocular sebaceous carcinomas can be assessed using the Union for International Cancer Control TNM staging system for skin carcinomas [ 3 ].…”
Section: Discussionmentioning
confidence: 99%